2020
DOI: 10.1021/acs.biomac.9b01730
|View full text |Cite
|
Sign up to set email alerts
|

Altered Thermal and Mechanical Properties of Spruce Galactoglucomannan Films Modified with an Etherification Reaction

Abstract: Native hemicellulose lacks many of the properties that make fossil fuel-based polymers excellent for use in today's industrial products and processes. The mechanical and thermal properties of the hemicellulose can, however, be modified, and its processability increased. We functionalized galactoglucomannan to lower its glass transition temperature (T g ) and thereby increase its processability. The functionalization was achieved through an etherification reaction with butyl glycidyl ether used at three molar r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 21 publications
3
15
0
Order By: Relevance
“…The FT-IR spectra of the etherified hemicellulose films are shown as Figure 7 . The observed characteristics peaks of hemicellulose agree with those reported in literature, indicating successful extraction and modification [ 1 , 29 , 36 ]. More specifically, in the unetherified poplar hemicellulose, the C–O stretching vibration peak intensity at 1044 cm −1 was significantly weaker than that of the uronic acid –COO − stretching vibration peak intensity at 1415 cm −1 .…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The FT-IR spectra of the etherified hemicellulose films are shown as Figure 7 . The observed characteristics peaks of hemicellulose agree with those reported in literature, indicating successful extraction and modification [ 1 , 29 , 36 ]. More specifically, in the unetherified poplar hemicellulose, the C–O stretching vibration peak intensity at 1044 cm −1 was significantly weaker than that of the uronic acid –COO − stretching vibration peak intensity at 1415 cm −1 .…”
Section: Resultssupporting
confidence: 88%
“…Epoxides possess an unstable ternary ring containing oxygen, which causes electrons to fall off neighboring carbon atoms; thus, epoxides are reactive to the hydroxyl compound, hemicellulose. The etherification can reduce the solubility of the hemicellulose film, enhance its biodegradability, and improve its film-forming performance [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in the figure, each film with varying STMP addition has obvious stretching vibration peak of fatty alcohol (-OH) at about 3300 cm −1 , and the stretching vibration peak of alkane C-H at about 2900 cm −1 . At 1050 cm −1 , the stretching vibration peaks of C-O bond and C-C bond in hemicellulose or the bending vibration peaks of C-O (H) on sugar ring were observed, which was consistent with the structural characteristics of hemicellulose film reported in literature [15,20,32]. After the addition of STMP, three characteristic peaks of P/O bond appeared at 1260 cm −1 , 991 cm −1 and 759 cm −1 , and became more obvious with the increase of STMP addition, indicating the successful crosslinking of hemicellulose by STMP.…”
Section: Structure Analysis Of Stmp Crosslinked Hemicellulose Filmssupporting
confidence: 91%
“…However, due to the complexity and diversity of hemicellulose structure, the research on hemicellulose is still in its infancy [9][10][11]. The chemical modification methods of hemicellulose mainly include esterification [12][13][14], etherification [15][16][17], grafting [18,19] and crosslinking [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The thus-functionalized GGM showed significantly decreased water absorption, indicating an increased hydrophobicity. Meanwhile, through dynamic mechanical analysis, Härdelin and co-workers [ 53 ] found that the functionalization of GGM improved both thermal performance and mechanical properties of the modified film. The modified film showed a reduced glass transition temperature ( T g), which makes the film easier to process.…”
Section: Modification Of Hemicellulosementioning
confidence: 99%